Підходи до визначення поняття "електронний документ" - Кавюк, Катерина; Тимовчак-Максимець, Оксана (Видавництво Львівської політехніки, 2012)
Through the development of information technologies the concept of an electronic document is one of the main in the Documentation science. The article suggests various approaches to the definition of of the term "electronic document".
Keywords: електронний документ; електронна форма документа; машинний код; електронний носій; реквізити